Congenital Anomalies in Neonates: Findings from Six Baghdad Hospitals - Bassam M. Al-Musawi; Ali M. Khalid; Nadin A. Kamal; Maha Z. Muneer (مجلة كلية الطب)
Background: Birth defects are the leading cause of both neonatal and post-neonatal deaths, as an estimated 240,000 neonates die in their first month of life worldwide each year. In Iraq, local studies have shown varying frequencies and types of congenital anomalies.